2015
DOI: 10.5014/ajot.2016.017558
|View full text |Cite
|
Sign up to set email alerts
|

Head Lag in Infancy: What Is It Telling Us?

Abstract: OBJECTIVE. To investigate changes in head lag across postmenstrual age and define associations between head lag and (1) perinatal exposures and (2) neurodevelopment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…With the AI-aided autotracking process and the proposed data preprocessing, infants' skeletons can be captured on mobile videos without background and angle limitations and provide features for model recognition. A total of 42.4% of the preterm infants had head lag until term equilibrated age, and only 4% of the infants had the same symptoms at birth [8]. While head lag has proven to be a vital early warning sign and PTS is an easy and necessary neurologic examination, few studies have explored how technology could help identify it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the AI-aided autotracking process and the proposed data preprocessing, infants' skeletons can be captured on mobile videos without background and angle limitations and provide features for model recognition. A total of 42.4% of the preterm infants had head lag until term equilibrated age, and only 4% of the infants had the same symptoms at birth [8]. While head lag has proven to be a vital early warning sign and PTS is an easy and necessary neurologic examination, few studies have explored how technology could help identify it.…”
Section: Discussionmentioning
confidence: 99%
“…We chose PTS as an example for proof of concept because it is one of the essential items from HINE and an easy-to-use neurologic examination in clinics. Although head lag alone could not predict future NDI outcomes [8], infants with CP or neuromuscular disease usually showed early head lag [11]. Compared with low-risk infants, head lag was demonstrated as an early predictive biomarker of future communication delays and diagnosis of autism in children with autistic siblings [9,10].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 We found statistically significant differences in head lag and ventral suspension, which too align with other studies of infants born less than 30 weeks' gestation that showed persistence of head lag at term-equivalent age. 13…”
Section: Tone and Posturementioning
confidence: 99%